Studi Skala Efek Pada Uji Kuat Tekan Uniaksial Terhadap Batulempung Formasi Pulau Balang dan Formasi Balikpapan Di Samarinda - Eka Ely Febrianty; Tommy Trides; Shalaho Dina Devy (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
Rock mass is a volume of rock consisting of rock material in the form of minerals, texture, composition and also consisting of discontinuous planes, forming a material and interconnected with all elements as a unit. The rock mass itself is composed of several intact rocks which basically have isotropic, continuous and homogeneous properties. However, the conditions found in the field are different, namely anisotropic, discontinuous and heterogeneous. These properties will certainly influence the test results in the uniaxial test. There are several factors that influence the results of uniaxial rock tests, one of which is the scale effect. The purpose of this test is to determine and analyze the effect of rock sample size on the uniaxial compressive strength value of claystone. This rock testing was carried out at the Mineral and Coal Technology Laboratory and the rock sampling locations were in Palaran District, Samarinda City and in North Samarinda District, Samarinda City. In this uniaxial compressive strength test, 3 side widths with different lengths will be used. After carrying out the uniaxial compressive strength test, the average uniaxial compressive strength test value was obtained in each formation, such as the Balang Island formation, the average rock compressive strength test value was 1.68 Mpa and the Balang formation, the average rock compressive strength test value was 3.10. Mpa. Based on these results, it can be concluded that the larger the sample size, the smaller the rock compressive strength test value tends to be.